Knowledge and practices of parents of school age children towards Helminthiasis and malaria in northwestern Ethiopia - Abebe Animut; Berhanu Erko; Yohannes Negash; Abraham Degarege (BMC, 2024)
Abstract Background Helminthiasis and malaria prevail in developing countries including Ethiopia, where they claim lives, retard physical and mental growth, reduce productivity and contain economic growth. Implementing helminthiasis and malaria control strategies require adequate knowledge and practices of the affected communities. Knowledge and practices of parents of school age children was assessed in relation to risk of child infection with Helminthiasis and malaria. Methods A total of 398 parents of school age children attending Maksegnit Number Two Elementary School from September 2020 to June 2021 were interviewed regarding their sociodemography, knowledge and practice towards Helminthiasis and malaria. The risk of child infection with Helminthiasis and malaria in relation to sociodemography and household practices was tested using multivariable logistic regression model. Results Risk of child infection with Helminthiasis was lower when the responding parent was female (OR = 0.54; CI = 0.32-0.92) and monthly household income was ≥ 2001 birr (OR = 0.39; CI = 0.22-0.70). A monthly income of ≥ 2001 birr was associated with a low risk of child infection with malaria (OR = 0.37; CI = 0.21-0.65). Children living with married parents were at higher risk of Helminthiasis (OR = 2.25, CI = 1.33-3.81) and malaria (OR = 2.71, CI = 1.60-4.58) infection. Latrine with wooden floor was correlated with a high risk of child infection with Helminthiasis (OR = 7.2; CI = 2.16-23.95). While washing with soap after toilet (OR = 0.09; CI = 0.03-0.34) and eating washed cabbage/fruit (OR = 0.26; 0.15-0.44) were associated with a lower risk of infection. Parents who participated in environmental management based vector control were less likely to report child infection with malaria (OR = 0.44; 0.20-0.97). A child living in residual insecticide sprayed house was at risk of malaria infection (OR = 3.16; CI = 1.45-6.92). Conclusions In general female responding parent, higher household income, and washing with soap after toilet or eating washed cabbage/fruit were associated with decreased risk of intestinal helminthiasis infection in children. In addition, higher income and participation in enviroinmental management based vector contol were associated with decreased malaria infection risk in children.